New 1,2,4-Triazole Potential Inhibitors of Mycobacterial Imidazoleglycerol-Phosphate Dehydratase (IGPD) - Eugenia Oleynik; Ekaterina Pyankina; Ekaterina Mitina; Ekaterina Mikhina; Andrey Matveev (Chemistry Proceedings)
A number of new 5-aminomethyl-1,2,4-triazole-3-carboxamides, demonstrating high model affinity to the IGPD catalytic site comparable with that of the native substrate, were synthesized. The derivatives obtained were tested for antimicrobial potential against M. smegmatis, a species related to M. tuberculosis. During the initial antimicrobial activity evaluation in vitro, some compounds investigated inhibited microbial growth. Moreover, high binding energy values calculated for compounds/enzyme’s catalytic site complexes correlated with the compounds’ antimicrobial efficacy. This suggests that the probable biological action mechanism of new 5-aminomethyl-1,2,4-triazole-3-carboxamides may be based on their binding to the catalytic site of IGPD, which provides prerequisites for further study of this class of compounds as potential IGPD inhibitors.